Health Risks of Heavy Metals Exposure from Ballast Water - Deandra Amirah Najahrina (Lembaga Pengembangan Kinerja Dosen, 2026)
Ballast water plays a crucial role in maintaining ship stability during shipping, but it also carries environmental and human health risks due to the heavy metals it carries. This study aims to examine the health risks posed by exposure to heavy metals in ballast water and to assess the effectiveness of management practices implemented in the maritime industry. Using a literature review method, this study examines various scientific sources related to the content of heavy metals such as lead (Pb), cadmium (Cd), copper (Cu), and zinc (Zn) in ballast water, as well as their impacts on human health and marine ecosystems. The results indicate that heavy metals in ballast water can cause long-term toxic effects such as neurological disorders, kidney damage, and respiratory and reproductive disorders. The greatest risk is experienced by maritime workers who are directly exposed through inhalation or skin contact during the ballast water sampling and processing process. To minimize these risks, strict work safety protocols, improved ballast water treatment technology, and regular monitoring of heavy metal levels are required. Thus, this study emphasizes the importance of strengthening ballast water management policies and practices that are oriented towards human health and environmental sustainability.